Green synthesis of calcium carbonate nanoparticles using waste fruit peel extract. (2021) - Garg, Rajni; Kumari, Mamta; Kumar, Mandeep; Dhiman, Sourabh; Garg, Rishav
Abstract: Nanotechnology is a trending field that addresses the issues in the range of 1–100 nm. Due to their small size, orientation and physical properties, nanoparticles are used immensely and the output of any other substance that has contact with such small particles is reportedly altered. The various chemical, physical, and biological methods can easily be used for the preparation of these particles. However, the biological approach is the better approach, being eco-friendly, less time-consuming and cost-effective as well as simpler than the other approaches. This paper uses the aqueous extract of orange peel to reduce and enclose the green synthesis of calcium carbonate nanoparticles. The formation of nanoparticles has been shown to be obtained at a fixed ratio of plant extract and metal solution. FTIR, XRD and SEM analysis has been used to characterize the nanoparticles. The crystalline phase of calcium carbonate nanoparticles was identified as polymorphic phase. The study provided an easy technique to synthesize the nanoparticles for further use in various fields.